Fostering cultural competence: Exploring client perception in a health coaching intervention among college students - Oh, Seungbin; Benes, Sarah; Yan, Zi (Nursing & Health Sciences, 2024)
Health coaching could be an innovative approach to develop student coaches' cultural competence (CC) among future health professionals. The current mix-method study design explored the impact of an 8-week peer health coaching intervention among college students on CC, from both student health coaches (i.e., students majored in health sciences who completed health coaching training and acted as health coach) and student clients' perspective. Nine student coaches and 24 student clients participated in the study. The quantitative analysis showed an increase in the clients' perceived level of coaches' CC between the pre- and posttest. The qualitative analysis revealed three themes, including varying levels of awareness, respectful and culturally responsive coaching, and cultural connection. Implications and recommendations for educators and researchers are discussed.
Keywords: cultural competence; cultural humility; dept.hms; health coaching; mixed-method design; peer-reviewed

Perception of a Peer Health Coaching Intervention Among College Students: Client Experience - Benes, Sarah; Oh, Seungbin; Peacock, Jessica; Yan, Zi (American Journal of Health Education, 2023)
Keywords: dept.hms; peer-reviewed

The impact of an 8-week wellness peer coaching program on physical activity among college students: 1338 - Peacock, Jessica; Yan, Zi; Bowling, April; Benes, Sarah (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

An 8-week peer health coaching intervention among college students: a pilot randomized study - Yan, Zi; Peacock, Jessica; Cohen, Juliana F. W.; Kurdziel, Laura; Benes, Sarah; Oh, Seungbin; Bowling, April (Nutrients, 2023)
This study explored the effects of an 8-week peer coaching program on physical activity (PA), diet, sleep, social isolation, and mental health among college students in the United States. A total of 52 college students were recruited and randomized to the coaching (n = 28) or the control group (n = 24). The coaching group met with a trained peer health coach once a week for 8 weeks focusing on self-selected wellness domains. Coaching techniques included reflective listening, motivational interviews, and goal setting. The control group received a wellness handbook. PA, self-efficacy for eating healthy foods, quality of sleep, social isolation, positive affect and well-being, anxiety, and cognitive function were measured. No interaction effects between time and group were significant for the overall intervention group (all p > 0.05), while the main effects of group difference on moderate PA and total PA were significant (p < 0.05). Goal-specific analysis showed that, compared to the control group, those who had a PA goal significantly increased vigorous PA Metabolic Equivalent of Task (METs) (p < 0.05). The vigorous METs for the PA goal group increased from 1013.33 (SD = 1055.12) to 1578.67 (SD = 1354.09); the control group decreased from 1012.94 (SD = 1322.943) to 682.11 (SD = 754.89); having a stress goal significantly predicted a higher post-coaching positive affect and well-being, controlling the pre-score and other demographic factors: B = 0.37 and p < 0.05. Peer coaching showed a promising effect on improving PA and positive affect and well-being among college students.
Keywords: dept.hms; diet; mental health; peer-reviewed; physical activity; positive affect; sleep; stress